ANALISIS BANTUAN KREDIT DARI PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG EMAS SEMARANG TERHADAP PERKEMBANGAN USAHA MIKRO KECIL DI KOTA SEMARANG - Ardiyanto, Bagus; Hendra Setiawan, Achma (Diponegoro Journal of Economics, 2013)
Micro and Small Enterprises (MSEs) are the biggest players in the economic sector that engages in trading and services. In general, the problems faced by MSEs in the city of Semarang is the capital problem, in which micro entrepreneurs of small businesses do not have enough capital to do business. The research is purposed to analyze whether the credit service from PT Pelabuhan Indonesia III branch Tanjung Emas in Semarang is useful or not from the perspective of the capital difference, sales turnover, labor, and profit of MSEs before and after getting the credit service. The research use primary data collected from the interview to 30 samples of respondents (n = 30). Beside, secondary data is also used which are from the related organization and some literatures. This research was conducted in the City of Semarang, while the analyzing method used is Wilcoxon sign rank test. Based on calculation of wilcoxon sign rank p-value for capital variable obtained for 0,000 (0,000<0,05), which means there were differences in capital variable before and after credit service of PT Pelabuhan Indonesia III branch of Tanjung Emas in Semarang, or increased by 177%. For variable of sales turnover obtained a p-value of 0,000 (0,000<0,05), which means there were differences in sales turnover variable after credit service of PT Pelabuhan Indonesia III branch of Tanjung Emas in Semarang, namely an increase of 83%. Wilcoxon sign rank test for the labor variable showed p-value of 0,000 (0,000<0,05) which means there were a difference in labour (hours) on micro before and after credit service of PT Pelabuhan Indonesia III branch of Tanjung Emas in Semarang, where there was an increase of 6,3% of working hours. For profit variable, wilcoxon sign rank test showed a p-value 0,000 (0,000<0,05), which means there were a difference profit before and after credit service of PT Pelabuhan Indonesia III branch of Tanjung Emas in Semarang or increase by 188%.